ACORN — An Automated Coder of Report Narrative - Shapiro, P. A. (Methods of Information in Medicine, 1967)
An Automated Coder of Report Narrative (ACORN) is being developed by the Biostatistics Department at Roswell Park Memorial Institute for Cancer Research in Buffalo, New York. ACORN seeks to standardize and automatically structure the information contained in dictated narrative summaries in case histories — in this instance post-operative surgical reports. The approach is based on the string analysis of Zellig Harris. It takes advantage of the syntactical structure of the English language to extract the information and organize it in a form which is readily utilizable by techniques which are related to (but which are much more versatile than) current punch-card procedures. The over-all system of ACORN is complex and only about half of the entire system has been developed to the point where the programs can be tested on actual operative reports. The results to date are sufficiently interesting to warrant a preliminary progress report.Die biostatistische Abteilung des Roswell Park Memorial Institute for Cancer Research in Buffalo (N. Y.) entwickelt zur Zeit ein automatisches Codiersystem für in Umgangssprache abgefaßte Krankengeschichten, genannt ACORN (= Automated Coder Of Report Narrative). ACORN versucht, die in textlich frei gestalteten Zusammenfassungen von Operationsberichten enthaltene Information zu standardisieren und automatisch zu strukturieren. Die Methode basiert auf der Kettenanalyse von Zellig Harris. Sie nutzt die syntaktische Struktur der englischen Sprache, um die Information zu extrahieren und sie in eine Form zu bringen, die sie für den üblichen Lochkartenprozeduren ähnliche, aber vielseitigere Methoden auswertbar macht. Das Gesamtsystem ACORN ist komplex; bisher konnte lediglich etwa die Hälfte des Systems so weit entwickelt werden, daß die Programme an vorliegenden Operationsberichten getestet werden konnten. Die bisherigen Ergebnisse sind aber für eine vorläufige Mitteilung hinreichend interessant.